Епос кубанських козаків - Нирко, О. (Народна творчість та етнографія, 2005)
The following research depicts a great number of representatives of cossack epos on Kuban. The author offers some facts on the history of bandura playing in this territory, lists the biographies of famous players of the XIX-XX cc (K. Kravchenko, M. Varawa, V. Shevchenko and many others) as well as of some contemporary ones (D. Bilyj, V. Iljin). The article studies the players repertoire, the place of the genre of duma in it, popular topics of the songs, etc.